Artificial Intelligence in Higher Education: A Contemporary Examination of Illich’s Theories - Muhamad Nur Azmi Wahyudi (Journal of Teaching and Learning)
In an era where artificial intelligence (AI) increasingly permeates the educational sphere, Abubaker Qutieshat’s Artificial Intelligence in Higher Education: A Contemporary Examination of Illich’s Theories offers a timely and thought-provoking reflection on this shift's ethical, philosophical, and societal implications. Far from presenting AI as a mere technological tool, Qutieshat critically engages with the educational theories of Ivan Illich, challenging readers to reconsider the role of institutions, the meaning of learning, and the future of higher education. Through an interdisciplinary lens that merges medical education, cognitive psychology, and technological ethics, the author proposes a vision of AI not as a dominating force but as a convivial companion that can liberate or further entrench educational inequalities.